A Study of Faculty Governance Leaders’ Perceptions of Online and Blended Learning - Elizabeth Ciabocchi; Amy Patraka Ginsberg; Anthony G. Picciano (Online Learning, 2016)
This article reports the findings of a study on the perceptions of faculty governance leaders to online and blended learning. For the purposes of this study, faculty governance was defined as formally established bodies in colleges and universities such as senates, councils, and collective bargaining organizations that are affiliated with the American Association of University Professors (AAUP). While there have been many studies on the perceptions of students, faculty, and administrators, there has been very little research on the perceptions of faculty governance leaders who hold critical positions in colleges and universities. Governance leaders are at the crux of approval processes that influence the development of curricula, faculty personnel policies, and academic programs, all of which can impact the implementation of online and blended learning initiatives. The research methodology for this study included a survey sent to a sample of governance leaders at U.S. institutions of higher education and follow-up phone interviews or email correspondence with a small number of volunteers. The sample was identified using an American Association of University Professors (AAUP) membership list. The results of this study provide important new information on the perceptions of this influential group of leaders on matters related to online and blended learning.